Evaluation of a non‐pharmacological interdisciplinary pain rehabilitation and functional restoration program for chronic pain in veterans. (10th October 2022) - Ward, Ralph; Rauch, Sheila A. M.; Axon, Robert Neal; Saenger, Michael S.
Abstract: Objective: To conduct a quality improvement evaluation of the Empower Veterans Program (EVP), an interdisciplinary pain rehabilitation/functional restoration program option for functional restoration for high‐impact chronic pain, offered in a large metro‐area Veterans Health Administration (VHA) system. Data Sources: VHA Corporate Data Warehouse electronic medical record data for patients treated by EVP between 2015 and 2019. Evaluation Design: This retrospective design first compared EVP patients considered engaged or not engaged in completing treatment in terms of demographic characteristics and post‐treatment changes in clinical measures related to opioid use and mental health. We then compared mortality risk between matched groups of treated and untreated patients with chronic pain and concurrent opioid prescriptions using propensity score matching and Cox proportional hazards methods. "Treated" in the matched groups was defined as any level of EVP participation (i.e., both engaged and not engaged). Data Collection/Extraction Methods: We first identified 1053 EVP patients with 1 year of pre‐and post‐treatment follow‐time and determined their engagement level. From those with chronic pain and prescription opioids, we matched 237 EVP patients to 375 untreated patients. Principal Findings: Engaged patients (57.4% of treated patients), were somewhat older than the non‐engaged (mean age 57.1 vs. 53.7, Cohen's D = 0.30), and achieved lower mean PHQ9 depression scores in the post‐treatment year (9.2 vs. 10.6, Cohen's D = 0.20). Participation in EVP was associated with a 65% lower mortality risk among Veterans with chronic pain and opioid use when compared to the untreated patients: (HR: 0.35, 95% CI: 0.17, 0.75). Conclusions: EVP was associated with a large reduction in mortality risk for Veterans with both chronic pain and opioid use. This result could inform the decision process in a VA station or region when considering providing or expanding access to an interdisciplinary rehabilitation/functional restoration program for chronic pain.